Clear cell carcinoma arising in an ovarian remnant 19 years after oophoerctomy: case report - Ting-ting Yao; Shao-jie Zhao; Bing Zhang (BMC, 2023)
Abstract Background Ovarian remnant syndrome (ORS) is a rare complication that occurs after oophorectomy, characterized by residual ovarian tissue causing pelvic pain, masses, and various symptoms. The clinical manifestations of ORS are nonspecific, and its diagnosis relies on histological examination. Since ORS typically represents a benign ovarian lesion, there have been few reported cases of malignant transformation. In this report, we presented a unique case of ovarian clear cell carcinoma (OCCC) arising from an ovarian remnant following salpingo-oophorectomy. Case presentation Our patient was a 47-year-old female initially diagnosed with uterine myoma. She had previously undergone cesarean section and unilateral salpingo-oophorectomy. Transvaginal ultrasound and computed tomography (CT) scans revealed a soft tissue mass adjacent to the right lateral wall of the myometrium. The patient opted for transabdominal hysterectomy, left adnexal resection, laparoscopic omentectomy, appendectomy, and pelvic and abdominal lymphadenectomy. The final pathology results confirmed the diagnosis of OCCC, consistent with ORS. The patient subsequently received six cycles of intravenous chemotherapy using the carboplatin/paclitaxel (TC) regimen (paclitaxel liposomes 175 mg/m², carboplatin AUC 5). After 3 years of follow-up, the patient's condition remained normal. Conclusion ORS can significantly impact patients' quality of life and pose challenges for clinicians. Complete excision of ovarian tissue during the initial surgery is crucial in preventing ORS recurrence and potential malignant transformation of ovarian remnants.